Adapting to Space Limitations During Prone Real-Time Magnetic Resonance Imaging-Guided Stereotaxic Laser Ablation: Technical Pearls. Issue 4 (27th June 2019) - Zervos, Thomas M; Scarpace, Lisa; Robin, Adam M; Schwalb, Jason M; Air, Ellen L
Abstract: BACKGROUND: New techniques of intraoperative magnetic resonance imaging (MRI)-guided stereotaxy enable minimally invasive approaches to intracranial pathology. Laser interstitial thermal therapy (LITT), convection-enhanced drug delivery, and stereotactic biopsy can be performed with a real-time confirmation of location and the ability to adjust for intracranial shift during the procedure. However, these procedures are constrained by patient positioning and the need for trajectories that avoid collision between stereotactic elements and the small MRI bore. To our knowledge, this is the first report to outline the technical details of safe intraoperative MRI (iMRI)-guided stereotaxy, performed with prone positioning. OBJECTIVE: To present technical pearls to guide the safe conduction of iMRI-guided stereotaxy and LITT while in the prone position. METHODS: The details of the positioning and trajectories for a series of patients who underwent Clearpoint® (MRI Interventions Inc) frameless real-time MRI-guided stereotaxis using a posterior approach were reviewed. RESULTS: In this series, 5 patients underwent selective amygdalohippocampectomy, and 2 underwent tumor biopsy/ablation while in the prone position without any complications. CONCLUSION: Prone iMRI procedures can be performed safely even in a 60-cm MRI bore.